The post-cranial anatomy and functional morphology of Conoryctes comma (Mammalia: Taeniodonta) from the Paleocene of North America. - Zoi Kynigopoulou; Sarah L Shelley; Thomas E Williamson; Stephen L Brusatte (PLoS ONE)
Conoryctes comma is a member of the enigmatic group Taeniodonta, Paleogene mammals that have been found only in North America. Taeniodonts were part of the first wave of placental mammal diversification after the end-Cretaceous extinction. The lack of postcranial elements has limited the understanding of the anatomy and locomotion of Conoryctes, and how it compared to other taeniodonts. We here describe the postcranial anatomy and functional morphology of Conoryctes, based largely on nine new specimens found in the San Juan Basin, New Mexico, USA. The specimens include elements of the axial column, such as the axis, sacrum, and ribs; the humerus, ulna, radius, and part of the manus; the innominate, femur, tibia, and part of the pes, including the tarsals. Conoryctes was a medium-sized mammal, with a robust humerus, radius, and femur, and with anatomical similarities to other conoryctid taeniodonts and Onychodectes. The tarsal elements of Conoryctes show characteristics of the "leptictimorph astragalocalcaneal morphology" as seen in other Paleogene mammals, such as Escavadodon, Palaeanodon, and Procerberus. Anatomical features of the forelimb and hindlimb of Conoryctes indicate that it was a scratch-digging animal with powerful forearm muscles and well-stabilized digits, features that may have helped it adapt to the subtropical forests of the San Juan Basin, approximately 63 million years ago. This corroborates the previous hypothesis that digging adaptations are seen in all members of Taeniodonta for which the postcranial elements are known, and that digging ability was present in the common ancestor of the clade and potentially central to their radiation after the environmental destruction of the end-Cretaceous extinction.